SECULARISM AND THE HINDU WORLDVIEW - Agnivesh, Swami (Journal of Dharma, 2000)
Secularism" and "worldview" are both concepts that emerged from outside of the territorial context of the Vedic faith. The tools of thought and analysis that we use could be a limiting, sometimes misguiding, factor. This is especially true in the spiritual domain. The tendency to fit spiritual ideals into secular framework has limitations, not less than its practical uses.